Answer:
y=-3x+4
Explanation:
The slope-intercept form of the equation of a line is y=mx+b, where m is the slope and b is the y-intercept. To find the slope, use
![m=(y_2-y_1)/(x_2-x_1)](https://img.qammunity.org/2023/formulas/mathematics/high-school/78uaqhwt0aws3qfwxigaftpihnmb1gzxtp.png)
For this problem, let
![(x_1,y_1)=(1,1)\\(x_2,y_2)=(4,-8)](https://img.qammunity.org/2023/formulas/mathematics/high-school/d0g3jb74ceydezbqjl95jmgddf16hbzmqx.png)
So,
![m=((-8)-(1))/((4)-(1))\\m=(-8-1)/(4-1)\\m=(-9)/(3)\\m=-3](https://img.qammunity.org/2023/formulas/mathematics/high-school/funln8rjb7zfaxskw3e06e7u99twwsgm8x.png)
Let -3 equal m in the point-slope form
, and substitute any of the ordered pairs from the table. Let
![(x_1,y_1)=(1,1)](https://img.qammunity.org/2023/formulas/mathematics/high-school/vfui1fvttzx0x3cj9vnf5vxuixofm9i8vd.png)
So,
![y-(1)=(-3)(x-1)\\y-1=-3(x-1)](https://img.qammunity.org/2023/formulas/mathematics/high-school/h65kde6k34j2ofqmms9bwwck9fm40l8ou7.png)
Finally, manipulate the point-slope form of the equation of a line to derive the slope-intercept form:
![y-1=-3(x-1)\\y-1=-3x+3\\(y-1)+1=(-3x+3)+1\\y=-3x+4](https://img.qammunity.org/2023/formulas/mathematics/high-school/hdjmwfw7rlihl6hmznsq7s8d6iixi8aiex.png)